ASPEK HUKUM PENGAWASAN PELANGGARAN PEMUNGUTAN HONORARIUM NOTARIS OLEH DEWAN KEHORMATAN DAERAH NOTARIS (STUDI KASUS PERKARA PELANGGARAN KODE ETIK NOMOR :001/DKD/KLT/IV/2010) - , Maria Mahardhika Candra Gupitasari ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The Legal Aspects Research of Supervision on Notaryâs Honorarium Collection Infringement by Notary Regional Honorary Board (A Case Study of Ethics Code Violation Case Number: 001/DKD/KLT/IV/2010) is a study which discussed three things. The first is the supervision authority of the Regional Honorary Board on the honorarium collection infringement committed by the Notary as a result of the honorarium adjustment, which only set upper and lower limits, as of led to a lot of interpretation with unfair competition as the result. Second, the research discussed sanctions had been given on the honorarium collection infringement. Third, the research analyzed the honorarium infringement case which occurred in the ethics code infringement case verdict No. 001 / DKD/KLT/IV/2010. This study aimed to discover the Notaryâs Honorarium Collection Infringement Supervision and the consideration of sanctions against the honorarium infringement, as well as to analyze the decision verdict which made by the Notary Regional Honorary Board. This research was a normative legal research with an empirical approach research using primary data and secondary data sources. The research was presented with a descriptive report which was analyzed qualitatively The gathering results as follows: 1) The Notary Regional Honorary Board was authorized to investigate the honorarium infringement. The Notary Regional Honorary Board was able to quest infringement facts on their own idea or a written complaint from an association member or another person with convincing evidences that there had been an infringement of ethics code. 2) The basis for the sanctions consideration against the Notaryâs honorarium infringement built upon the offense severity was based on the compensation by Public Notary Profesion and Ethics Code. However, based on the contents of the two rules regarding sanctions, it was concerned on the rules in Ethics Code relating to the Honorarium collection. 3) Rules which regulated the amount of honorarium only set upper and lower limits so that complicated the supervision. On the contrary, the interpretation of this honorarium led to unfair competition among fellow Notaries was assumed based on certain agreements made by the own Notary as was the case in this research.